On the Determination of the Forming Limits of Low-Alloy Steel Thin-Walled Tubes - Magrinho João; Cruz Pedro; Sáenz-De-Argandoña Eneko; Mendiguren Joseba; Silva M. Beatriz (MATEC Web of Conferences)
This paper presents an innovative methodology to determine the formability limits of low-alloy steel tubes, with particular attention to the effects of the weld line on their performance. Digital Image Correlation (DIC) system, coupled with time-dependent methodologies is used to identify the onset of failure by necking and to measure the corresponding limit strains. Thickness measurements and gauge length strain analysis across cracked regions are employed to characterise the onset of fracture and to evaluate fracture limit strains. The methodology incorporates tensile tests in longitudinal and transversal directions and tube expansion tests using elastomers to generate strain loading paths and fracture strain pairs across a broad spectrum of forming conditions. These conditions range from biaxial stretching in the first quadrant to pure tension in the second quadrant of principal strain space. The unique influence of the weld line is highlighted, including its impact on both the Forming Limit Curve (FLC) and the Fracture Forming Line (FFL) plotted in the principal strain space. This study demonstrates, for the first time, the FFL of low-alloy steel thin-walled tubes, providing critical insights for optimising tube forming processes involving welded materials.